Irrigation water quality on the salinity and sodicity of soils in the São Gonçalo project - Cordeiro, Gilberto Gomes; Zylstra, Gerard; Millar, Agustin A. (Pesquisa Agropecuaria Brasileira, 2014)
In order to explain the influence of irrigation and drainage conditions on the salinity and sodicity built up on the alluvial soils of São Gonçalo Irrigation Project, some 25 points were selected widespread all over the area under operation for permanent sampling. Soil sampling, from 90 cm of depth, took place once a year during four consecutive years for determining the pH, CE and exchange cations. Ground (phreatic) water depth was also recorded once a month during a year in all the sampling sites, as well as irrigation water quality. No change was observed on the soil salinity and sodicity at the end of the study period. This is due, possibly, to a salt equilibrium achieved in the soil profile as a consequence of a certain degree of natural underground drainage towards the Piranhas river and to the relative good quality of the irrigation water.